Recent avian influenza virus A/H5N1 evolution in vaccinated and unvaccinated poultry from farms in Southern Vietnam, January-March 2010. - Long, N; Thanh, T; Van Doorn, H; Vu, P; Dung, P; Dung, T; Tien, T; Thao, D; Hung, P; Quang, N; Hoa, N; Bryant, J; et al. (2011)
We report 15 new avian influenza virus A/H5N1 haemagglutinin (HA) sequences sampled from visibly sick domestic poultry in southern Vietnam, between 1 January 2010 and 6 March 2010. These HA sequences form a new sub-clade of the clade 1 H5N1 viruses that have been circulating in Vietnam since 2003/2004. The viruses are characterized by a change from isoleucine to valine at position 514 (I514V) and are 1.8% divergent at the nucleotide level from HA sequences sampled in Vietnam in 2007. Five new amino acid changes were observed at previously identified antigenic sites, and three were located within structural elements of the receptor-binding domain. One new mutation removed a potential N-linked glycosylation site, and a methionine insertion was observed in one virus at the polybasic cleavage site. Five of these viruses were sampled from farms where poultry were vaccinated against H5N1, but there was no association between observed amino acid changes and flock vaccination status. Despite the current lack of evidence for antigenic drift or immune escape in Vietnamese H5N1 viruses, continued surveillance remains a high priority.